2023
DOI: 10.3389/fphys.2023.1148146
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle dysfunctions in pulmonary arterial hypertension: Effects of aerobic exercise training

Abstract: Pulmonary arterial hypertension is associated with skeletal muscle myopathy and atrophy and impaired exercise tolerance. Aerobic exercise training has been recommended as a non-pharmacological therapy for deleterious effects imposed by pulmonary arterial hypertension. Aerobic physical training induces skeletal muscle adaptations via reduced inflammation, improved anabolic processes, decreased hypoxia and regulation of mitochondrial function. These benefits improve physical exertion tolerance and quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…The underlying mechanisms of such exercise benefits, however, are not well determined, especially concerning skeletal muscles, since few studies on experimental models of PAH have evaluated the effect of exercise regimens (e.g., Moreira-Gonçalves et al, 2015 ; McCullough et al, 2020 ; Vieira et al, 2020 ). Despite the lack of studies, in a recent review ( Drummond et al, 2023 ), our group showed that aerobic exercise training can provide protection and reduce muscle atrophy, increase muscle capillarization and improve mitochondrial function. Nevertheless, we pointed out that studies on skeletal muscle’s structural, cellular and molecular adaptations to exercise are crucial for the development of effective preventive and/or therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms of such exercise benefits, however, are not well determined, especially concerning skeletal muscles, since few studies on experimental models of PAH have evaluated the effect of exercise regimens (e.g., Moreira-Gonçalves et al, 2015 ; McCullough et al, 2020 ; Vieira et al, 2020 ). Despite the lack of studies, in a recent review ( Drummond et al, 2023 ), our group showed that aerobic exercise training can provide protection and reduce muscle atrophy, increase muscle capillarization and improve mitochondrial function. Nevertheless, we pointed out that studies on skeletal muscle’s structural, cellular and molecular adaptations to exercise are crucial for the development of effective preventive and/or therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%